Edukasi Peran Penting Senam Sehat Jantung Untuk Meningkatkan Kesehatan Kardiorespirasi pada Lansia Di Kota Bandar Lampung - Zulfikar, Zulfikar; Maulana Ahsan Fadhail; Rinaldi Prima Saputra; Rina Mayangsari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aimed to analyze the role of health education integrated with Healthy Heart Exercise in improving cardiorespiratory health among older adults in Bandar Lampung City. The research employed a community based intervention using structured aerobic exercise combined with educational sessions tailored to elderly physiological characteristics. Cardiorespiratory parameters including resting heart rate, blood pressure, respiratory rate, and functional walking capacity were measured before and after the intervention to assess physiological adaptation. The results demonstrated consistent improvements across all indicators reflecting enhanced cardiovascular efficiency, better vascular regulation, and improved respiratory function. Beyond physiological outcomes, the educational component increased knowledge, motivation, and adherence, supporting sustainable physical activity behavior. Integrating exercise and education within a supportive community setting effectively optimized biological and behavioral responses. These findings indicate that Healthy Heart Exercise combined with health education is a feasible and effective promotive and preventive strategy to improve cardiorespiratory health in older adults, emphasizing the importance of educational reinforcement in community based activity programs nationwide.